2017
DOI: 10.1016/j.neuron.2016.11.044
|View full text |Cite
|
Sign up to set email alerts
|

lncRNA Functional Networks in Oligodendrocytes Reveal Stage-Specific Myelination Control by an lncOL1 /Suz12 Complex in the CNS

Abstract: Summary Long noncoding RNAs (lncRNAs) are emerging as important regulators of cellular functions, but their roles in oligodendrocyte myelination remain undefined. Through de novo transcriptome reconstruction, we establish dynamic expression profiles of lncRNAs at different stages of oligodendrocyte development and uncover a cohort of stage-specific oligodendrocyte-restricted lncRNAs, including a conserved chromatin-associated lncOL1. Co-expression network analyses further define the association of distinct oli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
115
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 115 publications
(124 citation statements)
references
References 52 publications
8
115
1
Order By: Relevance
“…It has been shown that Wave1/Wsf1 knockout in mice leads to fewer OL processes per cell and hypomyelination in the white matter (Kim et al, ). Despite the fact that no significant correlation was found between Pcdh17 and Pcdh17it expression by an earlier bioinformatics analysis (He et al, ), we discovered that they are largely co‐expressed in imOLs (Figure S5e,f; A. Fudge and H. Li unpublished observations). Taken together, the available evidence suggests that Pcdh17 might take part in the initiation of myelination by regulating f‐actin assembly while Pcdh17it might fine‐tune the level of Pcdh17 expression.…”
Section: Discussioncontrasting
confidence: 69%
See 2 more Smart Citations
“…It has been shown that Wave1/Wsf1 knockout in mice leads to fewer OL processes per cell and hypomyelination in the white matter (Kim et al, ). Despite the fact that no significant correlation was found between Pcdh17 and Pcdh17it expression by an earlier bioinformatics analysis (He et al, ), we discovered that they are largely co‐expressed in imOLs (Figure S5e,f; A. Fudge and H. Li unpublished observations). Taken together, the available evidence suggests that Pcdh17 might take part in the initiation of myelination by regulating f‐actin assembly while Pcdh17it might fine‐tune the level of Pcdh17 expression.…”
Section: Discussioncontrasting
confidence: 69%
“…We provide evidence that Pcdh17it is specifically expressed in imOLs and is present in cytoplasm and/or nucleus (Figure ). Pcdh17it (also known as 9630013A20Rik or lncOL1 ) was reported to regulate OL differentiation through interaction with polycomb repressive complex 2 (Prc2) via Suz12 (He et al, ). The Pcdh17it gene lies inside intron 1 of the Pcdh17 gene (encoding cell–cell adhesion molecule Protocadherin 17), in the antisense direction, on mouse chromosome 14.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Emerging evidence indicates that lncRNAs not only participate in autoimmune diseases including systemic lupus erythematosus (SLE), rheumatoid arthritis (RA) and psoriasis [25-27], but also play important roles in CNS development, homeostasis, stress responses, and plasticity [28]. Recent work points to the role of lncRNAs in oligodendrocyte precursor cell (OPC) differentiation from neural stem cells (NSCs), myelination and remyelination in the CNS [29, 30]. lncRNA (Malat1) displays anti–apoptotic and anti-inflammatory roles in microvasculature structure of the brain to reduce ischemic brain injury [31].…”
Section: Discussionmentioning
confidence: 99%
“…Histone methyltransfereases (HMT) like Ezh2 in the PRC2 complex can cause chromatin compaction by trimethylation of histone K27, which leads to a repressive state . Ezh2 has been shown to promote murine oligodendrocyte proliferation from NSCs in vitro [Sher et al ., 2008], while deletion of the murine Ezh2 in Olig1 + early progenitors led to dramatic reduction in mature oligodendrocytes and myelination in mice .…”
Section: Atp‐dependent Remodelers In Oligodendrocyte Specification Lmentioning
confidence: 99%